2019
DOI: 10.1088/1361-665x/ab2b60
|View full text |Cite
|
Sign up to set email alerts
|

Operational range of a ferrofluid pocket bearing

Abstract: Ferrofluid pocket bearings are interesting for fast and precise positioning systems thank to the absence of stick-slip, the low viscous friction and their cost-effective nature. However, the characteristics of the bearing change due to over(de)compression since air escapes out of the enclosed pocket. This article presents an experimentally validated model that includes the air mass inside the pocket in the calculation of the equilibrium position of the ferrofluid bearing. Moreover, a simple and efficient way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…18 FF pocket bearings are an interesting application for fast and precise positioning systems, thanks to the absence of the stick-slip phenomenon, low viscous friction and the fact they are always self-aligning. 19 The phenomenon of magnetic fluid attraction to a permanent magnet is used, for example, in a micro rotarylinear actuator used in minimally invasive active catheters. 20 Another example of use is in rolling bearings.…”
Section: Lubrication Using a Ffmentioning
confidence: 99%
See 1 more Smart Citation
“…18 FF pocket bearings are an interesting application for fast and precise positioning systems, thanks to the absence of the stick-slip phenomenon, low viscous friction and the fact they are always self-aligning. 19 The phenomenon of magnetic fluid attraction to a permanent magnet is used, for example, in a micro rotarylinear actuator used in minimally invasive active catheters. 20 Another example of use is in rolling bearings.…”
Section: Lubrication Using a Ffmentioning
confidence: 99%
“…18 FF pocket bearings are an interesting application for fast and precise positioning systems, thanks to the absence of the stick-slip phenomenon, low viscous friction and the fact they are always self-aligning. 19…”
Section: Lubrication Using a Ffmentioning
confidence: 99%
“…Recent studies have shown that the bearing force of the magnetized MF is about 20 times higher than that of the traditional liquid bearing [14]. In addition to the MF support, the gas sealed by MF can also generate a supporting force [15,16]. Then, can the lifting force be used to control the stick-slip behavior and what is the essential mechanism?…”
Section: Introductionmentioning
confidence: 99%
“…These ferrofluid bearings have the characteristics of simple structure, controllable viscosity and good anti-friction, which lay a theoretical foundation for the intelligentization of manufacturing industry. [5][6][7] Rosensweig 8 proposed a mechanical model for the ferrofluid's magnetic field forces calculation. The results showed that the oil film viscosity of the ferrofluid bearings was affected by the magnetic flux density, which provided a theoretical basis for the research of the ferrofluid bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrofluid bearings are a kind of sliding bearing with ferrofluid as damping medium, which can realize controllable damping. These ferrofluid bearings have the characteristics of simple structure, controllable viscosity and good anti‐friction, which lay a theoretical foundation for the intelligentization of manufacturing industry 5–7 …”
Section: Introductionmentioning
confidence: 99%